Comercio internacional en el Sur Global. Jerarquías, conexiones y agrupaciones a través del análisis de redes sociales - Elkin Argiro Muñoz-Arroyave; Alexandra López-Martínez; Luis David Marín-Zapata; Alejandro Zapata-Ortiz (Revista Iberoamericana de Estudios de Desarrollo)
International trade can be a source of resources for developing countries; however, it is essential to analyse the trade partners that are accessed. Thus, the objective of the article is to analyse the social networks made up of international trade between the countries of the Global South and the way in which Latin America can take advantage of these opportunities for its development. A quantitative methodology based on the social network analysis technique is used. It is concluded that the network is marked by the geographical proximity between the countries of the Global South; likewise, Latin America has an incipient process of economic integration that could be further exploited, as well as expanding its participation in the markets of the Global South.